The utility of fistulography in the diagnosis of thyroglossal duct cyst with fistulous tract: Case report and literature review - Honghua Zhu, MD; Baijuan Gong, MD, PhD; Chegmin Han, MD; Zhimin Li, MD, PhD; Allan G. Farman, BDS, PhD, MBA, DSc; William C. Scarfe, BDS, MS, FRACDS (Radiology Case Reports, 2015)
Thyroglossal duct cyst (TGDC) is one of the most common congenital, midline, cervical lesions originating from an embryonic thyroglossal duct remnant. It is usually diagnosed clinically. Imaging is used to confirm the clinical diagnosis, and fistulography is very helpful in the diagnosis and surgical planning for thyroglossal fistulous tract. Fistulographs show the direction, length, and anatomy of the remnant tracts and the small tracts connecting a TGDC to the tongue base at the foramen cecum. This report presents a case of TGDC in a 12-year-old boy and demonstrates the utility of fistulography imaging in the diagnosis of TGDC with fistulous tract. In this case, fistulography was performed after cannulating the external opening of the fistula. The patient underwent a resection, including thyroglossal tract removal and further excision of the mid portion of the hyoid bone (the Sistrunk procedure). The postoperative pathology report indicated thyroglossal duct remnants with no evidence of malignancy.